(untitled) (Research, Society and Development, 2023)
Sporotrichosis is a mycosis of great medical and veterinary relevance in Brazil, since it presents aggravating epidemiological data, especially in Rio de Janeiro, where there are high endemic rates. This disease is caused by the thermodymorphic fungus of the genus Sporothrix and has two transmission routes, one being sapronotic/classical, acquired by inoculation traumas through accidents with plant organic matter, and the other zoonotic/alternative, through scratches and bites of infected domestic felines, the latter being of great importance on the epidemiology of the disease in Brazil. Sporothrix brasiliensis, the most virulent species of the clinical clade, plays an important role in epidemiological studies in the country, being associated with the spread between domestic cats and humans. However, there is still little knowledge about this disease among pet owners, which makes the treatment of diagnosed patients and the control of outbreaks even more difficult. The lack of knowledge about the measures to be taken or the appropriate prophylaxis contribute to the transmission reaching epidemic proportions. Therefore, it is essential to disseminate information about this fungus and the disease caused by it. The present study, therefore, aims to inform about sporotrichosis as one of the conditions that most affect cats within Veterinary Medicine. With this in mind, a literature review on this subject was conducted.